Synthesis of α-tetrasubstituted amino acids by solid phase ugi reaction using isocyanide amino acid derivatives as resin spacers - Ribeiro, Ana Isabel F. (2012)
Fundação para a Ciência e Tecnologia (Portugal) for financial support through project PTDC/QUI-BIQ/118389/2010 (FCOMP-01-0124-FEDER-020906) and PEstC/QUI/UI0686/2011 (F-COMP-01-0124-FEDER-022716), FEDER-COMPETE. The NMR spectrometer Bruker Avance III 400 is part of the National NMR Network and was purchased with funds from FCT and FEDER.